Familiarity for entities as a sensitive marker of antero-lateral entorhinal atrophy in amnestic mild cognitive impairment. (July 2020) - Besson, Gabriel; Simon, Jessica; Salmon, Eric; Bastin, Christine
Abstract: Alzheimer's disease (AD) symptomatology typically starts with memory deficits. Neurofibrillary tangles – one of the neuropathological hallmarks of AD – first affect the transentorhinal cortex (i.e., Brodmann's area 35 – BA35 and antero-lateral entorhinal cortex), a subregion of the antero-lateral parahippocampal region (also comprising BA36) currently hypothesized to serve as a functional hub representing entities. Here, we tested this hypothesis by investigating whether atrophy of antero-lateral parahippocampal subregions affects memory for entities. Patients with amnestic mild cognitive impairment (aMCI; known to be at high-risk of AD and to present with variable antero-lateral parahippocampal atrophy; N = 17) and healthy older control participants ( N = 17) underwent a high-resolution MRI scan of the antero-lateral parahippocampal subregions and a visual object familiarity task, critically including three conditions with increasing need for entity-level representation: (1) letting all fluency cues contribute to familiarity, (2) precluding conceptual fluency, and (3) also precluding perceptual fluency, thereby directly tapping familiarity for entities. In aMCI, right antero-lateral entorhinal cortex specifically contributed to familiarity for entities, an association that was stronger than with familiarity in the 'discriminative' condition (2) (also precluding conceptual fluency, but tested in a viewpoint-dependent fashion as traditionally). In contrast, right BA36 specifically contributed to familiarity in the discriminative condition, an association that appeared marginally stronger than with familiarity for entities. These results shed new light on the functional hierarchy that may exist within the antero-lateral parahippocampal hub. Importantly, familiarity requiring an entity-level representation may specifically target transentorhinal integrity, opening a promising avenue to develop the still-lacking clinical marker of AD-related initial decline.